Introduction to time series analysis and forecasting - Montgomery, Douglas C. (John Wiley & Sons, Inc., 2015)
Introduction to forecasting -- Statistics background for forecasting -- Regression analysis and forecasting -- Exponential smoothing methods -- Autoregressive integrated moving average (ARIMA) models -- Transfer functions and intervention models -- Survey of other forecasting methods -- Appendix A. Statistical tables -- Appendix B. Data sets for exercises